Neural correlates of emotional reactivity and regulation in youth with and without anxiety. Issue 8 (1st April 2021) - Padgaonkar, Namita Tanya; Phuong Uy, Jessica; DePasque, Samantha; Galván, Adriana; Peris, Tara S.
Abstract: Background: Youth with anxiety disorders struggle with managing emotions relative to peers, but the neural basis of this difference has not been examined. Methods: Youth (Mage = 13.6; range = 8–17) with ( n = 37) and without ( n = 24) anxiety disorders completed a cognitive reappraisal task while undergoing functional magnetic resonance imaging. Emotional reactivity and regulation, functional activation, and beta‐series connectivity were compared across groups. Results: Groups did not differ on emotional reactivity or regulation. However, fronto‐limbic activation after viewing aversive imagery with and without regulation, as well as affect ratings without regulation, were higher for anxious youth. Neither group demonstrated age‐related changes in regulation, though anxious youth became less reactive with age. Stronger amygdala‐ventromedial prefrontal cortex connectivity related to greater anxiety in control youth, but less anxiety in anxious youth. Conclusion: Anxious youth regulated when instructed, but regulation ability did not relate to age. Viewing aversive imagery related to heightened fronto‐limbic activation even after reappraisal. Emotion dysregulation in youth anxiety disorders may stem from heightened emotionality and potent bottom‐up neurobiological responses to aversive stimuli. Findings suggest the importance of treatments focused on both reducing initial emotional reactivity and bolstering regulatory capacity.